Diabetes Mellitus, Acute Hyperglycemia, and Ischemic Stroke - Bruno, Askiel (Current Science Inc., 2010)
Acute brain ischemia is a dynamic process susceptible to multiple modulating factors, such as blood glucose level. During acute ischemic brain injury, hyperglycemia exacerbates multiple deleterious derangements. Timely and sufficient correction of hyperglycemia during acute brain ischemia may limit the brain injury and improve clinical outcomes. The clinical efficacy of such intervention remains to be proven. Although results from animal and clinical observational studies suggest that hyperglycemia during acute brain ischemia may exacerbate the brain injury, there is no evidence from randomized treatment trials that rapid correction of the hyperglycemia improves outcomes. Given the excess effort, cost, and risk involved in rapid and safe correction of hyperglycemia during acute stroke, less aggressive treatments with subcutaneous insulin seem appropriate at this time. Subcutaneous insulin protocols can maintain blood glucose levels below 200 mg/dL a majority of the time in most patients, especially if basal insulin is added. When available, an endocrinology consultant can optimize the acute treatment and help the transition to long-term care. Given the multiple reports linking admission hyperglycemia with symptomatic hemorrhagic conversion of ischemic stroke treated with thrombolytic drugs, it may be best to rapidly lower severe hyperglycemia in such patients. For example, if the admission blood glucose is approximately 300 mg/dL and the patient is a candidate for thrombolytic therapy, consider giving an intravenous bolus of regular insulin 8 units. Somewhat lower or higher insulin doses may be best for lesser or greater hyperglycemia. Such a bolus will start lowering the blood glucose in about 5 min. A temporary continuous intravenous insulin infusion may then be used in most patients to maintain the glucose closer to normal levels (eg, below 180 or 140 mg/dL).